Reanalyzing the genetic history of Kra-Dai speakers from Thailand and new insights into their genetic interactions beyond Mainland Southeast Asia - Changmai, Piya; Phongbunchoo, Yutthaphong; Kočí, Jan; Flegontov, Pavel (Scientific reports, 2023)
Thailand is a country where over 60 languages from five language families (Austroasiatic, Austronesian, Hmong-Mien, Kra-Dai, and Sino-Tibetan) are spoken. The Kra-Dai language family is the most prevalent, and Thai, the official language of the country, belongs to it. Previous genome-wide studies on Thailand populations revealed a complex population structure and put some hypotheses forward concerning the population history of the country. However, many published populations have not been co-analyzed, and some aspects of population history were not explored adequately. In this study, we employ new methods to re-analyze published genome-wide genetic data on Thailand populations, with a focus on 14 Kra-Dai-speaking groups. Our analyses reveal South Asian ancestry in Kra-Dai-speaking Lao Isan and Khonmueang, and in Austroasiatic-speaking Palaung, in contrast to a previous study in which the data were generated. We support the admixture scenario for the formation of Kra-Dai-speaking groups from Thailand who harbor both Austroasiatic-related ancestry and Kra-Dai-related ancestry from outside of Thailand. We also provide evidence of bidirectional admixture between Southern Thai and Nayu, an Austronesian-speaking group from Southern Thailand. Challenging some previously reported genetic analyses, we reveal a close genetic relationship between Nayu and Austronesian-speaking groups from Island Southeast Asia (ISEA).
Keywords: Thajsko; Američané asijského původu; Language; Thailand; Asian People; Asian; lidé; Genome-Wide Association Study; jazyk (prostředek komunikace); jihovýchodní Asie; Asia, Southeastern; celogenomová asociační studie; Asijci; Humans